Revisión sistemática sobre la reducción de efectos emocionales negativos en trabajadores del área de emergencias y catástrofes mediante técnicas de catarsis - Prieto-Callejero, Blanca; Gómez-Salgado, Juan; Alvarado-Gómez, Francisco; Dias, Adriano [UNESP]; García-Iglesias, Juan Jesús; Ruiz-Frutos, Carlos (Associacio catalana de Salut Laboral, 2020)
AIM: To analyze catharsis techniques used with professionals assisting victims of emergencies and disasters. METHODS: Systematic review carried out in seven bibliographic databases: MEDLINE-Pubmed, Web of Science, Cochrane Library, CINAHL, Scopus, PsycINFO, and other secondary sources, for articles published between 2008 and 2017, with the terms catharsis, emergencies, debriefing y post-traumatic stress. Publication and selection biases were taken into account. RESULTS: Five reviews met the study inclusion criteria. Distress and traumatic experiences following an emergency or disaster are very common among health professionals, with adverse repercussions at the physical, psychological and cognitive levels. Some authors find that debriefing offers an opportunity for emotional release and toreduce the impact of stress on the lives of emergency responders, acting as a support network where they can reconstruct their experiences, express their thoughts and feelings, and reduce the impact on their lives. For other authors, however, this technique is not always effective for all professionals and may lead to negative consequences. CONCLUSIONS: Debriefing is a common intervention that promotes catharsis. However, there is considerable controversy over its implementation and effectiveness. This study identified a diversity of catharsis techniques applied to staff responding to emergencies and disasters.

OBJETIVO: Analizar las técnicas de catarsis empleadas en los trabajadores que atienden situaciones de emergencias y catástrofes. MÉTODOS: Revisión sistemática realizada en 7 bases de datos bibliográficas Medline-Pubmed, Web of Science, Cochrane Library, CINAHL, Scopus, PsycINFO y otras fuentes secundarias, para artículos publicados entre 2008 y 2017, con los términos «catarsis», «emergencias», «debriefing» y «estrés post-traumático». RESULTADOS: Los criterios de inclusión fueron cumplidos por 5 artículos. Los estudios muestran que es común entre el personal sanitario la exposición al sufrimiento y a las experiencias traumáticas, suponiendo repercusiones negativas manifestadas a nivel físico, psicológico y cognitivo tras situaciones de emergencias y catástrofes. Para algunos autores, el debriefing ofrece un lugar para descargar las emociones y reducir el impacto del estrés en la vida de los trabajadores de emergencia actuando como una red de apoyo para que dichos trabajadores puedan reconstruir sus experiencias y verbalizar sus pensamientos y sentimientos, así como reducir el impacto en sus vidas. Para otros en cambio, esta técnica no es eficaz para todos los profesionales y su uso puede conllevar consecuencias negativas. CONCLUSIONES: El debriefing es una intervención breve que promueve la catarsis. Sin embargo, existe una gran controversia sobre su eficacia y la manera de aplicar esta intervención. Este estudio pone de manifiesto la heterogeneidad existente en la aplicación de técnicas de catarsis en los trabajadores que atienden situaciones de emergencia y catástrofes.
Systematic Review of the Reduction of Negative Emotional Effects in Emergency and Disaster Response Workers Through Catharsis Techniques